Comparative structural analysis on the mitochondrial DNAs from various strains of Lentinula edodes - Kim, Sinil; Eom, Hyerang; Nandre, Rutuja; Choi, Yeon Jae; Lee, Hwayong; Ryu, Hojin; Ro, Hyeon-Su (Frontiers in Microbiology, 2022)
The evolution of mitochondria through variations in mitochondrial DNA (mtDNA) is one of the intriguing questions in eukaryotic cells. In order to assess the causes of the variations in mitochondria, the mtDNAs of the 21 strains of Lentinula edodes were assembled for this study, and analyzed together with four published mtDNA sequences. The mtDNAs were within the sizes of 117 kb ~ 122 kb. The gene number was observed consistent except for two mtDNAs, which carry a duplicated trnG1-trnG2 unit or a putative gene deletion. The size variation was largely attributed to the number of introns, repeated sequences, transposable elements (TEs), and plasmid-related sequences. Intron loss and gain were found from cox1, rnl, and rns of three mtDNAs. Loss of two introns in cox1 of KY217797.1 reduced its size by 2.7 kb, making it the smallest cox1 gene (8.4 kb) among the cox1s of the 25 mtDNAs, whereas gain of a Group II intron (2.65 kb) and loss of a Group I intron (1.7 kb) in cox1 of MF774813.1 resulted in the longest cox1 (12 kb). In rnl of L. edodes, we discovered four intron insertion consensus sequences which were unique to basidiomycetes but not ascomycetes. Differential incorporation of introns was the primary cause of the rnl size polymorphism. Homing endonucleases (HEGs) were suggestively involved in the mobilization of the introns because all of the introns have HEG genes of the LAGRIDADG or GIY-YIG families with the conserved HEG cleavage sites. TEs contributed to 11.04% of the mtDNA size in average, of which 7.08% was LTR-retrotransposon and 3.96% was DNA transposon, whereas the repeated sequences covered 4.6% of the mtDNA. The repeat numbers were variable in a strain-dependent manner. Both the TEs and repeated sequences were mostly found in the intronic and intergenic regions. Lastly, two major deletions were found in the plasmid-related sequence regions (pol2-pol3 and pol1-atp8) in the five mtDNAs. Particularly, the 6.8 kb-long deletion at pol2-pol3 region made MF774813.1 the shortest mtDNA of all. Our results demonstrate that mtDNA is a dynamic molecule that persistently evolves over a short period of time by insertion/deletion and repetition of DNA segments at the strain level.